Unveiling Patient Perspectives: A Multinational Cross-Sectional Analysis of Patient Experiences Undergoing Cleft Care by All-Women Surgical Teams - Tapia MF; Daradkeh H; Bustamante A; Jones EM; Treminio SY; Turk M; Rata M; Salazar B; Barkhordarzadeh AD; Bautista AC; Herrera Gomez L; Davis GL; et al. (Journal of Healthcare Leadership)
Maria Fernanda Tapia,1,2 Hebah Daradkeh,2,3 Atenas Bustamante,2 Emily Marie Jones,2 Sonia Y Treminio,2 Marvee Turk,2,4 Mikyla Rata,2 Barbara Salazar,2 Ainaz Dory Barkhordarzadeh,2,5 Alyssa Caitlin Bautista,2 Laura Herrera Gomez,2,4 Greta L Davis,2 William Magee III,2,4,6 Naikhoba CO Munabi,2,7 Allyn Auslander2 1Plastic and Reconstructive Surgery, Hospital Obrero #1, La Paz, Bolivia; 2Operation Smile Inc., Virginia Beach, VA, USA; 3Plastic and Reconstructive Surgery, University Hospital of North Midlands NHS Trust, Stoke-on-Trent, UK; 4Division of Plastic and Reconstructive Surgery, Keck School of Medicine of the University of Southern California, Los Angeles, CA, USA; 5David Geffen School of Medicine, University of California Los Angeles, Los Angeles, CA, USA; 6Division of Plastic and Maxillofacial Surgery, Children’s Hospital Los Angeles, Los Angeles, CA, USA; 7Division of Plastic and Reconstructive Surgery, New York Presbyterian-Columbia University Irving Medical Center, New York, NY, USACorrespondence: Laura Herrera Gomez, Division of Plastic and Reconstructive Surgery, Keck School of Medicine of the University of Southern California, 1510, San Pablo St, Suite 415, Los Angeles, CA, 90033, USA, Email Laura.herreragomez@med.usc.eduBackground: Although women provide approximately 75% of healthcare globally, they are underrepresented in healthcare leadership, surgery, and anesthesia. Patient- provider gender concordance has been shown to improve patient experience in high-income settings; however, patients in low-and middle-income countries often lack the opportunity to choose the gender of their provider and there is a paucity of literature on the importance of women healthcare providers in these settings.Aim: To assess the experiences and provider gender preferences of patients with cleft and their caregivers before and after receiving care from an all-women surgical team in a Women in Medicine (WIM) surgical program.Methods: This cross-sectional study is based on an anonymous survey administered to patients 15 years or older or their caregivers after receiving care from an all-women surgical team during four distinct cleft surgery programs in Morocco, Peru, Malawi, and the Philippines throughout 2022. Analysis included quantitative, descriptive statistics, chi-squared and f-tests.Results: Before the program, 20% of participants had never received care from women physicians and only 35% preferred women as their healthcare provider. After the program, 66% preferred women as their healthcare provider (p< 0.001) with the highest proportion in Morocco (90%) and lowest in Malawi and the Philippines (55%). Across all education levels, most participants preferred women after the program (64%) and 98% were satisfied or more than satisfied with the care received. The three most influential characteristics for preferring women were their understanding, patience, and communication.Conclusion: Participation in the WIM program provided some patients with their first opportunity to experience receiving care from a woman. This exposure may influence their preference for a healthcare provider, which has been shown to enhance patient experience. Programs like this are imperative to increasing visibility of women in surgical and healthcare leadership roles, improving patient experience, and increasing access to care.Keywords: cleft lip, patient satisfaction, health services accessibility, workforce diversity